Small mammals (Insectivora, Rodentia, Lagomorpha) from the Early Pleistocene hominin-bearing site of Dmanisi (Georgia). Issue 170 (September 2022) - Agustí, Jordi; Chochishvili, Giorgi; Lozano-Fernández, Iván; Furió, Marc; Piñero, Pedro; de Marfà, Roger
Abstract: Small mammals (insectivores, rodents, and lagomorphs) from Dmanisi are here reviewed for the first time and used as a tool for paleoenvironmental proxies. The small mammal faunal list is composed of shrews ( Beremendia fissidens, cf. Beremendia minor, Crocidura kornfeldi ), hamsters ( Cricetulus sp., Allocricetus bursae ), gerbils ( Parameriones aff. obeidiyensis ), murids ( Apodemus cf. atavus ), arvicolids ( Mimomys pliocaenicus, Mimomys aff. pusillus ), and pikas ( Ochotona sp.). A paleoenvironmental reconstruction based on the habitat weighting method has been applied to the rodent assemblage. According to this method, the most common elements indicate an open-dry habitat (36.5%), followed by water edge (25.7%) and rocky (21.0%) elements. Open-wet (15.5%) and woodland elements (1.3%) are rare. Therefore, the habitat occupied by the hominids of Dmanisi was characterized by the prevalence of arid conditions, from steppe or semi-desert to open Mediterranean forest, with stony or rocky substrate and bushy areas. The presence of permanent aquatic environments is also documented. From a biogeographic point of view, the small mammal community from Dmanisi is composed mainly by Western or Central Asian elements, with a poor representation of European elements ( Mimomys, Apodemus ). It is concluded that Dmanisi hominins most possibly had ecological requirements which were different from those of the Early Pleistocene hominins from Western Europe, which settled on wetter habitats. It could be also possible that Dmanisi hominins entered Southern Caucasus at an interglacial phase before the deposition of the Dmanisi site.